Estimativa de parâmetros estruturais de áreas de produção de eucalipto através de imagens de satélite na região de Botucatu /SP - Barros, Bruna Soares Xavier de [UNESP] (Universidade Estadual Paulista (Unesp), 2013)
Neste estudo se utilizou imagens de satélites multiespectrais como fonte de dados para determinação de parâmetros estruturais de uma floresta de eucalipto. Baseando-se em procedimentos utilizados em outras áreas de florestas de monocultura, através de uma metodologia que otimiza a monitoração e controle de um povoamento. A utilização dos Sistemas de Informação Geográfica (SIG), já é realidade presente em vários setores das atividades e necessidades humanas, devido principalmente a capacidade de armazenamento de dados e a velocidade na apresentação deste nas tomadas de decisões. Neste contexto, a avaliação de áreas de cultura de eucalipto, por meio de imagens aéreas, pode tornar muito rápida e acertada as tomadas de decisões pelas áreas técnicas ligadas ao cultivo e também pela área econômica. Este trabalho teve como objetivo verificar a possibilidade de determinar parâmetros estruturais através da avaliação de uma área de povoamento de eucalipto na região do município de Botucatu/SP Brasil, utilizando-se imagens satélite LANDSAT, ferramenta SIG e técnicas de análise estatística. Para avaliações da área plantada e os cálculos necessários foram utilizados imagens digitais Landsat 5/TM adquiridas junto ao U.S. Geological Survey /Earth Resources Observation &...

This work utilized multispectral satellite images as source of data for determination of structural parameters of an eucalyptus forest, based on procedures used in other areas of monoculture forests, through a methodology that optimizes the monitoring and control of a stand. The use of Geographic Information Systems (GIS) is already a reality in many sectors of human activities and needs, mainly due to storage capacity and data speed in delivering this in decision making. This work aimed at verifying the possibility to determine structural parameters by evaluating an area of eucalyptus plantation in Botucatu / SP Brazil, using Landsat satellite images, GIS tool, and statistical analysis techniques. For reviews of the planted area and the necessary calculations Landsat 5/TM digital images acquired from the U.S. Geological Survey / Earth Resources Observation & Science Center (EROS) were used, as well as forest inventory data for analysis in the field. The verification of the developed method proceeded through the characterization of the structures of culture, from the integration Landsat 5/TM image and field data, statistical procedures were done correlating the degree of linear dependence among variables and biometric digital, obtained by Index Normalized Difference Vegetation and reflectance for determination of the basal area, volume and biomass, by multiple linear regression. Using softwares: PCI Geomatics (version 9.1), Microsoft Office Excel 2007; Idrisi Kilimanjaro; ArcGis 10 Desktop and R (version 3.0.0). Atmospheric effects and little radiometric variability of the area are presented as the main limitations of the study. After analyzing the statistical model with the best fit regression obtained from ...
Keywords: Eucalipto; Engenharia florestal; Florestas - Medição; Levantamentos de recursos naturais; Satelites artificiais; Pesquisa florestal; Levantamentos florestais; Análise de imagem; Sensoriamento remoto; Forestry research